Pollen mixing in pollen generalist solitary bees: a possible strategy to complement or mitigate unfavourable pollen properties?. (24th January 2014) - Eckhardt, Michael; Haider, Mare; Dorn, Silvia; Müller, Andreas; Ings, Thomas
Summary Generalist herbivorous insects, which feed on plant tissue that is nutritionally heterogeneous or varies in its content of secondary metabolites, often benefit from dietary mixing through more balanced nutrient intake or reduced exposure to harmful secondary metabolites. Pollen is similarly heterogeneous as other plant tissue in its content of primary and secondary metabolites, suggesting that providing their offspring with mixed pollen diets might be a promising strategy for pollen generalist bees to complement nutrient imbalances or to mitigate harmful secondary metabolites of unfavourable pollen. In the present study, we compared larval performance of the pollen generalist solitary bee species Osmia cornuta (Megachilidae) on five experimental pollen diets that consisted of different proportions of unfavourable pollen diet of Ranunculus acris (Ranunculaceae) and favourable pollen diet of Sinapis arvensis (Brassicaceae). In addition, we microscopically analysed the pollen contained in the scopal brushes of field‐collected females of O. cornuta and three closely related species to elucidate to what degree these pollen generalist bees mix pollen of different hosts in their brood cells. In striking contrast to a pure Ranunculus pollen diet, which had a lethal effect on most developing larvae of O. cornuta, larval survival, larval development time and adult body mass of both males and females remained nearly unaffected by the admixture of up to 50% of Ranunculus pollen diet to the larval food. Between 42% and 66% of all female scopal pollen loads analysed contained mixtures of pollen from two to six plant families, indicating that pollen mixing is a common behaviour in O. cornuta and the three related bee species. The present study provides the first evidence that the larvae of pollen generalist bees can benefit from the nutrient content of unfavourable pollen without being negatively affected by its unfavourable chemical properties if such pollen is mixed with favourable pollen. We conclude that the widespread pollen mixing by females of pollen generalist bees should also be considered as a possible strategy to exploit flowers with unfavourable pollen and to optimize larval food quality.